2021
DOI: 10.2991/ahsr.k.210115.083
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effect of Citrus Sinensis Extract on Malondialdehyde (MDA) Levels in Rat Induced by Cigarette Smoke

Abstract: Cigarette smoke contains numerous substances containing free radicals and can prompt oxidative pressure. The buildup of free radicals cannot be neutralized by antioxidants for essential cancer prevention agent supplements from outside. In relation to that, the peel of citrus sinensis is expected to contain cell reinforcements that may eliminate free radicals. This study aims to determine the potential effect of Citrus sinensis peel extract on MDA levels in rats induced by cigarette smoke. This investigation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Food supplementation with CAFS to diabeticinduced rats in the present studies notably declined the levels of serum, hepatic as well as pancreatic lipid peroxides. This observation is consistent with Ochuko et al (2012) in tissues of the brain of diabetic rats was reported after treatment with a certain plant fiber and also Setyawati and Hidayati (2021), who reported decreased in MDA concentration after treating rat induced by cigarette smoke with orange peel (Citrus sinensis) extract. This effect could be traced to the free radical scavenging and antioxidant potentials of CAFS.…”
Section: Serum Hepatic and Pancreatic Vitamin E Concentrationssupporting
confidence: 91%
“…Food supplementation with CAFS to diabeticinduced rats in the present studies notably declined the levels of serum, hepatic as well as pancreatic lipid peroxides. This observation is consistent with Ochuko et al (2012) in tissues of the brain of diabetic rats was reported after treatment with a certain plant fiber and also Setyawati and Hidayati (2021), who reported decreased in MDA concentration after treating rat induced by cigarette smoke with orange peel (Citrus sinensis) extract. This effect could be traced to the free radical scavenging and antioxidant potentials of CAFS.…”
Section: Serum Hepatic and Pancreatic Vitamin E Concentrationssupporting
confidence: 91%